Role of fluorescent pseudomonads in the suppression of root rot and damping-off of cotton - J.P. VERMA, G.S. LAHA and (Indian Phytopathology, 2002)
Forty eight fluorescent Pseudomonas isolates were established from the rhizosphere of different species of cotton. Sixteen of these isolates inhibited the growth of Rhizoctonia solani in dual culture on Pseudomonas agar for fluorescein (PAF). In most cases the antagonistic effect was drastically reduced in ferric chloride-amended PAF medium indicating the production of some antifungal compound(s) only under iron-limiting conditions. All these 16 isolates produced volatile cyanides. The volatile metabolites produced by 5 isolates, FP-25, FP-28, FP-33, FP-43 and FP-47, significantly suppressed growth of R. solani. In cotton seed treatment tests, the disease incidence was significantly less with isolates FP-43, FP-47 and FP-28. Isolate FP-43 and FP-47 reduced the disease to 10% and 24%, respectively, from 88% in the control treatment. Isolate FP-28 reduced the disease to\36%.